Legal Responsibility of Hootsuite in the Crime of MIS-Use Personal Data - Inna Ayu Romadhona; Sekaring Ayumeida Kusnadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Data protection can basically relate specifically to privacy to determine whether information about them will be communicated or not to other parties (information privacy) regarding personal information. There are many crimes that use personal data, but this is not comparable to the understanding of the public who understand that personal data is prone to misuse by irresponsible parties. This research aims to examine the protection of personal data according to Law Number 27 of 2022 concerning Protection of Personal Data (hereinafter referred to as the PDP Law). The research uses normative legal research methods with a literature review, and the approach used is a statutory and conceptual approach with primary and secondary legal materials. Based on the results of this study, personal data protection is an overall effort to protect personal data in a series of personal data processing in order to guarantee the constitutional rights of personal data subjects. The urgency of the need for protection of personal data considering that personal data is still prone to misuse in society. Thus, in an effort to maximize the protection of personal data, a "Digital Revolution" is needed as an innovation effort to be able to develop various options in the realm of personal data protection such as storing, manipulating, transmitting volumes of data in real time , extensive and complex. A digital revolution characterized by a blend of technologies that blur the lines between the physical, digital and biological fields which has enabled the birth of various emerging technological breakthroughs in the fields of Information and Electronic Transactions consisting of newly discovered data and super-sophisticated computing power.